Preparation method and application of coal-based hard carbon negative electrode material
By pulverizing, pickling, pre-carbonizing, steam activation and high-temperature carbonizing the coal-based materials, the porosity and specific surface area of the coal-based hard carbon negative electrode materials are optimized, and the shortcomings of existing materials in sodium storage capacity and first-time Coulomb efficiency are solved, and higher charge and discharge capacity and first-time effect are achieved.
Patent Information
- Application Number
- CN202411856241.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
Smart Images

Figure BDA0005191885130000131 
Figure BDA0005191885130000141 
Figure BDA0005191885130000142
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a preparation method and application of a coal-based hard carbon negative electrode material. Background Art
[0002] Sodium-ion batteries have become a new type of secondary battery that has attracted widespread attention due to their abundant raw materials, low cost, environmental friendliness, and excellent rate and high and low temperature performance. Their potential application in large-scale energy storage has attracted a large number of researchers and companies to develop them.
[0003] As an important component of sodium-ion batteries, negative electrode materials have received increasing attention in recent years. Among them, carbon-based negative electrode materials have the characteristics of high conductivity, good structural stability, high sodium storage capacity, environmental protection and economy, which have laid a good foundation for the commercialization and wide application of sodium-ion batteries. Carbon-based negative electrode materials can be divided into two categories according to the degree of graphitization: graphite carbon and amorphous carbon. Compared with graphite carbon, amorphous carbon has low sodium storage potential and good cycle stability, so it shows great advantages. Among them, hard carbon negative electrode materials prepared with coal-based materials as precursors have unique advantages. Coal-based materials are abundant in resources and low in price. The cost of preparing coal-based hard carbon negative electrode materials is low. However, due to the complex composition of coal-based materials themselves and the uncertainty of the preparation process, the prepared coal-based hard carbon negative electrode materials often have uneven pore size and distribution, as well as a high measured specific surface area, resulting in low sodium storage capacity. The first coulombic efficiency is not ideal, so it is difficult to use for commercial applications. In order to increase the sodium storage capacity of coal-based hard carbon negative electrode materials and optimize the first coulombic efficiency, it is necessary to increase the porosity and control the pore size and the measured specific surface area while ensuring the uniform distribution of pores on the coal-based hard carbon negative electrode materials. However, an increase in porosity often means an increase in specific surface area. Therefore, there is an urgent need for a method that can further control the pore size and specific surface area while increasing the porosity of coal-based hard carbon negative electrode materials and ensuring uniform distribution of pores, so as to obtain coal-based hard carbon negative electrode materials with good charge and discharge capacity and first coulombic efficiency. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a coal-based hard carbon negative electrode material and a preparation method and application thereof, which effectively solves the problems of low sodium storage capacity and unsatisfactory first coulombic efficiency when preparing hard carbon negative electrode materials from traditional coal-based materials, and obtains a coal-based hard carbon negative electrode material with good charge and discharge capacity and first coulombic efficiency.
[0005] In a first aspect, the present invention provides a method for preparing a coal-based hard carbon negative electrode material using a coal-based material as a raw material:
[0006] S1: crushing and deashing the coal-based material, and then pre-carbonizing it to obtain a coal-based hard carbon negative electrode material matrix;
[0007] S2: Activate the coal-based hard carbon negative electrode material matrix at 750°C-1000°C by 0.1ml / min-5ml / min of activator steam for 0.5-5h;
[0008] S3: carbonizing the steam-activated coal-based hard carbon negative electrode material matrix at a high temperature of 1300-1800° C. and cooling the matrix to obtain a coal-based hard carbon negative electrode material;
[0009] The preparation conditions satisfy X=(A-750) / 50+B+C, 2≤X≤7, A>750, Y=(D-1300) / 100, 0≤Y≤3, wherein X is a steam activation factor, A is an activation temperature (°C), B is an activation time (h), C is an activator flow rate (ml / min), Y is a high-temperature carbonization factor, and D is a high-temperature carbonization temperature (°C).
[0010] In the second aspect, the present invention also provides a method for preparing a coal-based hard carbon negative electrode material, which can also be used as a method for designing the preparation condition parameters of a coal-based hard carbon negative electrode material, wherein the crushed coal-based material is acid-washed and pre-carbonized, and then steam activated and high-temperature carbonized to obtain a coal-based hard carbon negative electrode material; during the preparation process, the target coal-based hard carbon negative electrode material is obtained by controlling the difference between [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the measured specific surface area to be less than 3, thereby realizing the selection of steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters, that is, S 实 =[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z, wherein X=(A-750) / 50+B+C, Y=(D-1300) / 100, 2≤X≤7, A>750, 0≤Y≤3, X is the steam activation factor, A is the activation temperature (°C), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high temperature carbonization factor, and D is the high temperature carbonization temperature (°C).
[0011] As a further solution, the coal-based material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite, and lignite.
[0012] As a further solution, in step S1, the coal-based material crushing particle size is selected from Dv50=5-45 μm, for example, it can be any one of 5 μm, 10 μm, 15 μm, 25 μm, 35 μm, and 45 μm.
[0013] As a further solution, in step S1, the coal-based material crushing particle size is selected from Dv50=5-15 μm.
[0014] As a further solution, the pulverizing method in step S1 is not limited, and technicians can select a corresponding pulverizing method according to actual needs, such as ball milling, roller milling, ultrasonic pulverizing, and electromagnetic pulverizing.
[0015] As a further solution, in step S1, the coal-based material is deashed by pickling.
[0016] As a further solution, during the pickling process, the pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid.
[0017] As a further solution, the mass ratio of the pickling solution to the coal-based material is selected from (3-7):1.
[0018] As a further solution, after the pickling is completed, the pickled coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is considered to be completed and the material is dried.
[0019] As a further solution, the pre-carbonization in step S1 is performed under an inert atmosphere.
[0020] As a further solution, the inert atmosphere is selected from any one of argon and nitrogen.
[0021] As a further solution, the pre-carbonization heating rate in step S1 is selected from 2°C / min-5°C / min.
[0022] As a further solution, in step S1, the pre-carbonization temperature is selected from 500-1000°C.
[0023] As a further solution, the pre-carbonization temperature in step S1 is selected from 600-800°C.
[0024] As a further solution, in step S1, the pre-carbonization time is selected from 1-5 hours.
[0025] As a further preference, the pre-carbonization time in step S1 is selected from 2-4 hours.
[0026] As a further solution, in step S2, the activator vapor is selected from deionized water vapor.
[0027] As a further solution, in step S2, the steam-activated carrier gas is selected from any one of argon and nitrogen.
[0028] As a further solution, in step S2, the heating rate is selected from 5°C / min-15°C / min.
[0029] As a further solution, the high-temperature carbonization in step S3 is performed in an inert atmosphere, and the inert atmosphere is selected from any one of argon and nitrogen.
[0030] As a further solution, the heating rate in step S3 is selected from 3°C / min-8°C / min.
[0031] As a further solution, the cooling temperature in step S3 is selected from 70°C-25°C.
[0032] As a further solution, the high temperature carbonization time in step S3 is selected from 2h-6h.
[0033] As some preferred schemes, the activation temperature A is selected from 850℃-1000℃, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-3ml / min, and the high-temperature carbonization temperature D is selected from 1300℃-1600℃.
[0034] As some preferred schemes, the activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C.
[0035] Compared with the prior art, the present invention has at least the following beneficial effects:
[0036] The present invention provides an innovative preparation method specifically for coal-based hard carbon negative electrode materials. By precisely regulating the activation factor X and the carbonization factor Y, we can effectively control the degree of activation reaction and the shrinkage of pores during high-temperature carbonization, thereby achieving control over the specific surface area of the material, and further optimizing the porosity and micropore ratio of the coal-based hard carbon negative electrode material. When the coal-based hard carbon negative electrode material prepared by this scheme is used in a battery, it can effectively improve the first coulombic efficiency and the first week reversible capacity of the battery, solving the problem that the first coulombic efficiency and the first week reversible capacity cannot be taken into account when traditional coal-based materials are used to prepare hard carbon negative electrodes. At the same time, the coal-based hard carbon negative electrode material has low cost and simple preparation process, and therefore has good prospects for commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0038] Figure 1 This is a SEM image of the coal-based hard carbon negative electrode material prepared in Example 1;
[0039] Figure 2This is a charge and discharge curve diagram of the coal-based hard carbon negative electrode material prepared in Example 3;
[0040] Figure 3 This is the XRD pattern of the coal-based hard carbon negative electrode material prepared in Example 3;
[0041] Figure 4 This is the Raman spectrum of the coal-based hard carbon negative electrode material prepared in Example 8. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the accompanying drawings. Embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0043] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0044] Unless otherwise specified, the materials, reagents, devices, etc. used in the following examples can be obtained from commercial sources or prepared according to methods in public literature.
[0045] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0046] The following are terms or word definitions, and unless otherwise defined, all technical and scientific terms used herein are
[0047] In this article, the term "theoretical specific surface area" as used herein refers to the specific surface area calculated by S 理
[0048] =[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] to calculate the specific surface area.
[0049] In this article, the term "measured specific surface area S" is used herein. 实 " refers to the specific surface area obtained by actual testing of coal-based hard carbon anode materials through BET.
[0050] As used herein, the term "specific surface area" refers to the surface area per unit mass of the coal-based hard carbon negative electrode material.
[0051] In a first aspect, the present invention provides a method for preparing a coal-based hard carbon negative electrode material using a coal-based material as a raw material:
[0052] S1: crushing and deashing the coal-based material, and then pre-carbonizing it to obtain a coal-based hard carbon negative electrode material matrix;
[0053] S2: Activate the coal-based hard carbon negative electrode material matrix at 750°C-1000°C by 0.1ml / min-5ml / min of activator steam for 0.5-5h;
[0054] S3: carbonizing the steam-activated coal-based hard carbon negative electrode material matrix at a high temperature of 1300-1800° C. and cooling the matrix to obtain a coal-based hard carbon negative electrode material;
[0055] The preparation conditions satisfy X=(A-750) / 50+B+C, 2≤X≤7, A>750, Y=(D-1300) / 100, 0≤Y≤3, wherein X is a steam activation factor, A is an activation temperature (°C), B is an activation time (h), C is an activator flow rate (ml / min), Y is a high-temperature carbonization factor, and D is a high-temperature carbonization temperature (°C).
[0056] First, compared with other raw materials, coal-based materials are expected to be widely used in commercialization due to their low cost. However, the existing hard carbon negative electrode materials prepared from coal-based materials often have poor performance in both capacity and initial efficiency. This may be because the coal-based materials themselves have complex components and the carbonization process is difficult to control, resulting in uneven structure of the carbonized products, making it difficult to exert their own advantages. Therefore, in view of the unique properties of coal-based materials, the present invention proposes a preparation method specifically for coal-based hard carbon negative electrode materials: first, the crushed coal-based materials are acid-washed and pre-carbonized, the pre-carbonized coal-based materials are activated by steam, and the coal-based hard carbon negative electrode materials are obtained by high-temperature carbonization after activation;
[0057] Through acid washing, the coal-based materials can be purified and the influence of ash in the coal-based materials on subsequent operations can be reduced. Subsequently, through pre-carbonization, pores can be initially constructed on the coal-based materials. However, the matrix porosity of the coal-based hard carbon negative electrode material prepared by pre-carbonization alone often cannot meet the demand, and the proportion of micropores is low. For negative electrode materials, if you want to improve the capacity and efficiency of negative electrode materials, improving porosity and increasing the proportion of micropores are the key. Steam activation is a method of reacting steam with carbon inside the material to convert the internal carbon into CO or CO 2The method of producing pores by discharging in the form of steam can further optimize the pores initially constructed on the surface of the coal-based hard carbon negative electrode material through steam activation. By controlling the activation temperature A, activation time B, and activator flow rate C during the activation process, the porosity and uniformity in the coal-based hard carbon negative electrode material can be effectively improved. For steam activation, the activation temperature A is often related to the activation rate. A higher A often means that more carbon is consumed in the same time, so the porosity is higher. At the same time, the activation time B reflects the degree of reaction. The longer the activation time, the farther the steam can reach, so more deep pores will be generated, thereby improving the uniformity of the structure of the coal-based hard carbon negative electrode material. The activator flow rate C means that when the activation time and temperature are determined, a higher activator flow rate will allow the carbon material to contact more steam molecules, thereby increasing the specific surface area. In order to improve the porosity of the coal-based hard carbon negative electrode material and obtain more micropores and a lower specific surface area, it is necessary to control the activation temperature A, activation time B, and activation time C. Taking the activation factor X and the flow rate C of the agent into comprehensive consideration, when the activation factor X satisfies 2≤X≤7, the prepared hard carbon negative electrode material has a higher porosity and a pore size and specific surface area that are easier to optimize; although the adjustment of X can control the structure of the coal-based hard carbon negative electrode material to a certain extent, it is far from enough for the current demand for the capacity of the coal-based hard carbon negative electrode material. Therefore, the high-temperature carbonization method is also introduced into the preparation of the coal-based hard carbon negative electrode material. After the coal-based hard carbon negative electrode material matrix with uniform pore distribution and moderate pore size is initially prepared by steam activation, during the high-temperature carbonization process, on the one hand, the high temperature can convert more graphite structures and improve the conductivity of the coal-based hard carbon negative electrode material. On the other hand, in the high-temperature environment, the uniform pores initially prepared by steam activation are further optimized and reduced along with the growth of graphite microcrystals, thereby obtaining more micropores and reducing the specific surface area. When the carbonization temperature is greater than or equal to 1300°C, that is, the carbonization factor Y is selected from 0-3, we can obtain a coal-based hard carbon negative electrode material with a higher micropore ratio and a lower specific surface area.
[0058] In the second aspect, the present invention also provides a method for preparing a coal-based hard carbon negative electrode material, which can also be used as a method for designing the preparation condition parameters of a coal-based hard carbon negative electrode material, wherein the crushed coal-based material is acid-washed and pre-carbonized, and then steam activated and high-temperature carbonized to obtain a coal-based hard carbon negative electrode material; during the preparation process, the target coal-based hard carbon negative electrode material is obtained by controlling the difference between [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the measured specific surface area to be less than 3, thereby realizing the selection of steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters, that is, S 实=[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z, wherein X=(A-750) / 50+B+C, Y=(D-1300) / 100, 2≤X≤7, A>750, 0≤Y≤3, X is the steam activation factor, A is the activation temperature (°C), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high temperature carbonization factor, and D is the high temperature carbonization temperature (°C).
[0059] Through the method proposed in the first aspect, we obtained a coal-based hard carbon negative electrode material. During the preparation process, we found an interesting phenomenon. There is a certain correlation between the condition parameters in the preparation method and the specific surface area of the obtained coal-based hard carbon negative electrode material. When the steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters are substituted into [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and controlled [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96], the results are consistent with the actual When the difference between the measured specific surface areas is less than 3, we can obtain the target coal-based hard carbon negative electrode material; therefore, we can directly use the preparation condition parameters that satisfy the above-mentioned correlation relationship to obtain the required target material. At the same time, we can also obtain a method for designing coal-based hard carbon negative electrode material parameters based on the above-mentioned correlation relationship. By controlling the difference between the result [0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96] and the actual measured specific surface area to be less than 3, we can also achieve specific selection of steam activation temperature, steam activation time, activator flow rate, and high-temperature carbonization temperature parameters.
[0060] As a further solution, the coal-based material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite, and lignite.
[0061] As a further solution, the coal-based material crushing particle size in step S1 is selected from Dv50=5-45μm particle size, for example, it can be any one of 5μm, 10μm, 15μm, 25μm, 35μm, and 45μm. The coal-based material crushing particle size that satisfies Dv50=5-45μm is helpful to form more uniformly distributed preliminary pores during the pre-carbonization process on the one hand, and on the other hand, it can cooperate with steam activation to obtain a coal-based hard carbon negative electrode material with more pores and a higher number of defects.
[0062] As a further solution, in step S1, the coal-based material crushing particle size is selected from Dv50=5-15μm. The particle size of 5-15μm helps to further cooperate with steam to achieve activation of the coal-based hard carbon negative electrode material matrix, thereby increasing the number of pores and defects.
[0063] As a further solution, the pulverizing method in step S1 is not limited, and technicians can select a corresponding pulverizing method according to actual needs, such as ball milling, roller milling, ultrasonic pulverizing, and electromagnetic pulverizing.
[0064] As a further solution, the coal-based material is deashed by pickling in step S1. The composition of the coal-based material itself is relatively complex. Pickling the coal-based material can, on the one hand, remove impurities in the coal-based material, such as ash and / or minerals, improve the purity of the coal-based material, and improve the efficiency of subsequent steam activation and high-temperature carbonization; on the other hand, pickling to remove ash and / or minerals can also expose more defects in the coal-based material and increase the porosity, so as to facilitate the subsequent pre-carbonization, steam activation and high-temperature carbonization, and optimize the pores and specific surface area of the coal-based material, thereby obtaining a coal-based hard carbon negative electrode material with better charge and discharge capacity.
[0065] As a further solution, during the pickling process, the pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid.
[0066] As a further solution, the mass ratio of the pickling solution to the coal-based material is selected from (3-7):1.
[0067] As a further solution, after the pickling is completed, the pickled coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is considered to be completed and the material is dried.
[0068] As a further solution, the pre-carbonization in step S1 is performed under an inert atmosphere.
[0069] As a further solution, the inert atmosphere is selected from any one of argon and nitrogen.
[0070] As a further solution, the pre-carbonization heating rate in step S1 is selected from 2°C / min-5°C / min.
[0071] As a further solution, in step S1, the pre-carbonization temperature is selected from 500-1000°C.
[0072] As a further solution, the pre-carbonization temperature in step S1 is selected from 600-800°C.
[0073] As a further solution, in step S1, the pre-carbonization time is selected from 1-5 hours.
[0074] As a further preference, the pre-carbonization time in step S1 is selected from 2-4 hours.
[0075] As a further solution, in step S2, the activator vapor is selected from deionized water vapor.
[0076] As a further solution, in step S2, the steam-activated carrier gas is selected from any one of argon and nitrogen.
[0077] As a further solution, in step S2, the heating rate is selected from 5°C / min-15°C / min.
[0078] As a further solution, the high-temperature carbonization in step S3 is performed in an inert atmosphere, and the inert atmosphere is selected from any one of argon and nitrogen.
[0079] As a further solution, the heating rate in step S3 is selected from 3°C / min-8°C / min.
[0080] As a further solution, the cooling temperature in step S3 is selected from 70°C-25°C.
[0081] As a further solution, the high temperature carbonization temperature in step S3 is selected from 2h-6h.
[0082] As some preferred schemes, the activation temperature A is selected from 850℃-1000℃, the activation time B is selected from 1h-3h, and the activator flow rate C is selected from 0.5ml / min-3ml / min, which helps to form more defects and more and deeper pores. At the same time, the control of the activator flow rate to 0.5ml / min-3ml / min can also effectively control the pore diameter, providing a better foundation for subsequent high-temperature carbonization. On this basis, the high-temperature carbonization temperature D is selected from 1300℃-1600℃, which helps to further improve the optimization effect of temperature on pore diameter.
[0083] As some preferred schemes, the activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C. In the process of steam activation of coal-based hard carbon negative electrode materials, when A is selected from 800℃-900℃, since the steam activation process is an endothermic reaction, the activation temperature of 800℃-900℃ helps to promote the reaction rate and form more pores; at the same time, when the activation time is selected from 1h-3h and the activator flow rate is selected from 0.5ml / min-1ml / min, more deep pores and lower specific surface area can be obtained, which lays a good foundation for high-temperature carbonization. Therefore, the high-temperature carbonization temperature D can be selected from 1300℃-1500℃. Therefore, the activation temperature A is selected from 800℃-900℃, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300℃-1500℃, which helps to obtain coal-based hard carbon negative electrode materials with higher charge and discharge capacity.
[0084] In a third aspect, the present invention also provides a coal-based hard carbon negative electrode material prepared by the above method, wherein the coal-based hard carbon negative electrode material has a specific surface area of 5-200 m 2 / g, and the second week discharge curve satisfies 2.50≤N≤4.00, wherein N represents the capacity ratio of the platform area to the slope area in the second week discharge curve, the platform area refers to the portion of the discharge curve where the voltage is less than 0.1V, and the slope area refers to the portion of the discharge curve where the voltage is greater than 0.1V.
[0085] The area of coal-based hard carbon anode materials is mainly affected by steam activation and high-temperature carbonization. On the one hand, during steam activation, steam reacts with carbon materials to release CO 2 or CO, leaving pores. The generation of pores often means an increase in specific surface area. However, when the surface area exceeds 200m 2 The specific surface area of 5-200 m / g may cause excessive consumption of sodium ions. Therefore, it is necessary to control the coal-based hard carbon anode material by high-temperature carbonization. Under the combined action of steam activation and high-temperature carbonization, the coal-based hard carbon anode material exhibits a surface area of 5-200 m / g. 2 / g of specific surface area, which improves the initial efficiency of coal-based hard carbon negative electrode materials; at the same time, steam activation and high-temperature carbonization conditions will also affect the defects and pore size on the coal-based hard carbon negative electrode materials, and then affect the ratio of the capacity of the platform area and the slope area of the second week charge and discharge curve. In the discharge curve of the hard carbon negative electrode material of the sodium ion battery, the sodium storage mechanism in the slope area is related to the adsorption of sodium ions by the surface defects of the hard carbon and the insertion of sodium ions in the microcrystalline layers of the hard carbon graphite; while the platform area is attributed to the filling of sodium in the hard carbon micropores. In this scheme, the coal-based hard carbon negative electrode material that has been crushed, pickled and pre-carbonized needs to be steam activated to optimize the initially established pores. A large number of pores are introduced through the reaction of steam and carbon materials, which improves the sodium storage capacity. Furthermore, the pore structure of the coal-based hard carbon negative electrode material is optimized again through high-temperature carbonization, thereby introducing a large number of micropores, which improves the capacity of the platform area in one fell swoop, so that the coal-based hard carbon negative electrode material exhibits excellent charge and discharge capacity.
[0086] As some preferred solutions, the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g, the discharge curve of the second week satisfies 3≤N≤4, when the specific surface area of the coal-based hard carbon negative electrode material is selected from 5-50m 2 / g, which helps to further improve the first efficiency of coal-based hard carbon negative electrode materials. At the same time, the coal-based hard carbon negative electrode materials whose second-week discharge curve satisfies 3≤N≤4 mean higher micropore filling ability, and therefore show higher charge and discharge capacity.
[0087] As a further solution, the ratio of the D peak to the G peak area in the Raman spectrum test of the coal-based hard carbon negative electrode material is D / I G1.70-1.90, total pore volume ≤ 0.034cm 3 / g, the proportion of micropore volume with pore diameter less than 2nm to the total pore volume of the material is ≥10%.
[0088] In Raman spectroscopy, the D peak is usually related to defects in carbon materials, and the appearance of the D peak often indicates the presence of a disordered structure in the material; while the G peak usually indicates the sp 2 The in-plane stretching vibration of the hybrid can be used to provide information on the crystallinity and grain size of the material; D / I G On the one hand, it shows the proportion of defects in the material, and on the other hand, it also characterizes the degree of graphitization in the coal-based hard carbon negative electrode material; the coal-based hard carbon negative electrode material prepared by this scheme shows I D / I G The value is 1.70-1.90, which may be because the steam activation process introduces a large number of defects, thereby improving the adsorption capacity of the coal-based hard carbon anode material surface for sodium ions. On the other hand, the high-temperature carbonization process will promote the growth of graphite microcrystals, so the coal-based hard carbon anode material shows I D / I G 1.70-1.90; secondly, pore size and porosity are also important factors affecting the electrochemical performance of coal-based hard carbon anode materials. In the coal-based hard carbon anode materials prepared in this scheme, the total pore volume is ≤0.034cm 3 / g, the proportion of micropore volume with pore size <2nm to the total pore volume of the material is ≥10%, which means that the coal-based hard carbon negative electrode material prepared by this scheme has a higher micropore (2nm) proportion and a higher porosity. This may be because pre-carbonization and steam activation create more pores for the coal-based hard carbon negative electrode material, and the subsequent high-temperature carbonization further optimizes the pore size of the coal-based hard carbon negative electrode material and increases the micropore proportion; the increase in the micropore proportion enhances the ability of the coal-based hard carbon negative electrode material to fill sodium ions, so the coal-based hard carbon negative electrode material exhibits a higher charge and discharge capacity.
[0089] As some preferred solutions, the coal-based hard carbon negative electrode material has a Raman spectrum test. D / I G Selected from 1.70-1.90, total pore volume ≤ 0.034cm 3 / g, the volume of micropores with a pore size of less than 2nm accounts for ≥20% of the total pore volume of the material, which helps to obtain coal-based hard carbon negative electrode materials with higher charge and discharge capacity and better first coulomb efficiency.
[0090] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0091] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0092] Example 1
[0093] The preparation steps of coal-based hard carbon negative electrode material are as follows:
[0094] S1: 30 g of bituminous coal raw material particles were ball-milled to a particle size of Dv50 = 5 μm, 4 mol / L hydrochloric acid, 4 mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30 g of the crushed bituminous coal raw material was pickled with 120 g of the mixed solution. After the pickling, the filtrate was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of the water washing. Then, it was dried for 12 hours, and under the protection of a nitrogen atmosphere, the temperature was raised to 750°C at a heating rate of 3°C / min for pre-carbonization for 3 hours to obtain a coal-based hard carbon negative electrode material matrix;
[0095] S2: Using nitrogen as carrier gas, water vapor was introduced to activate the coal-based hard carbon negative electrode material matrix in a tubular furnace. The temperature was raised to 900°C at a heating rate of 10°C / min for 1h, and the activator flow rate was 1ml / min.
[0096] S3: Under a nitrogen atmosphere, the steam-activated coal-based hard carbon negative electrode material matrix is activated by a tubular furnace, the temperature is raised to 1500°C at a rate of 5°C / min, the heat preservation time is 3h, and the temperature is cooled to 50°C to obtain a bituminous coal-based hard carbon negative electrode material.
[0097] Example 2-16
[0098] Some parameters in Example 1 were changed, and the parameter details are shown in Table 1. The remaining preparation steps and methods were the same as in Example 1.
[0099] Comparative Example 1
[0100] The specific steps and preparation method are the same as those in Example 1, except that walnut shells are used as the raw material for the hard carbon negative electrode material.
[0101] Comparative Example 2
[0102] S1: 30g of bituminous coal raw material particles were crushed to a particle size of Dv50 = 5μm, 4mol / L hydrochloric acid, 4mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30g of the crushed bituminous coal raw material was acid-washed with 120g of the mixed solution. After the acid washing, it was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of water washing, and a coal-based hard carbon negative electrode material matrix was obtained;
[0103] S2: Using nitrogen as carrier gas, water vapor was introduced to activate the coal-based hard carbon negative electrode material matrix - comparative example 1 in a tubular furnace, and the temperature was raised to 900°C at a heating rate of 10°C / min, and the activation was performed for 1h, and the flow rate of the activator was 1ml / min;
[0104] S3: Under a nitrogen atmosphere, the steam-activated coal-based hard carbon negative electrode material matrix is activated by a tubular furnace, the temperature is raised to 1500°C at a rate of 5°C / min, the heat preservation time is 3h, and the temperature is cooled to 50°C to obtain a bituminous coal-based hard carbon negative electrode material.
[0105] Comparative Example 3
[0106] S1: 30g of bituminous coal raw material particles were crushed to a particle size of Dv50 = 5μm, 4mol / L hydrochloric acid, 4mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30g of the crushed bituminous coal raw material was acid-washed with 120g of the mixed solution. After the acid washing, it was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of water washing. It was then dried for 12h, and under the protection of nitrogen atmosphere, the temperature was raised to 750℃ at a heating rate of 3℃ / min for pre-carbonization for 3h to obtain a coal-based hard carbon negative electrode material matrix;
[0107] S2: In a nitrogen atmosphere, the coal-based hard carbon negative electrode material matrix was activated by a tubular furnace, heated to 1500°C at a rate of 5°C / min, kept at this temperature for 3h, and cooled to 50°C to obtain a bituminous coal-based hard carbon negative electrode material.
[0108] Comparative Example 4
[0109] S1: 30g of bituminous coal raw material particles were crushed to a particle size of Dv50 = 5μm, 4mol / L hydrochloric acid, 4mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30g of the crushed bituminous coal raw material was acid-washed with 120g of the mixed solution. After the acid washing, it was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of water washing. It was then dried for 12h, and under the protection of nitrogen atmosphere, the temperature was raised to 750℃ at a heating rate of 3℃ / min for pre-carbonization for 3h to obtain a coal-based hard carbon negative electrode material matrix;
[0110] S2: Water vapor is introduced with nitrogen as carrier gas to activate the coal-based hard carbon negative electrode material matrix in a tubular furnace. The temperature is raised to 900°C at a heating rate of 10°C / min and activated for 1h. The flow rate of the activator is 1ml / min. After the activation, a bituminous coal-based hard carbon negative electrode material is obtained.
[0111] Comparative Example 5
[0112] S1: 30g of bituminous coal raw material particles were crushed to a particle size of Dv50 = 5μm, 4mol / L hydrochloric acid, 4mol / L nitric acid, and 10% hydrofluoric acid were mixed in a volume ratio of 3:1:2, and then 30g of the crushed bituminous coal raw material was acid-washed with 120g of the mixed solution. After the acid washing, it was washed with deionized water and then filtered until the filtrate met the pH>6, which was considered to be the end of water washing. It was then dried for 12h, and under the protection of nitrogen atmosphere, the temperature was raised to 750℃ at a heating rate of 3℃ / min for pre-carbonization for 3h to obtain a coal-based hard carbon negative electrode material matrix;
[0113] S2: In a nitrogen atmosphere, the coal-based hard carbon negative electrode material matrix is carbonized at high temperature in a tubular furnace, the temperature is increased to 1500°C at a rate of 5°C / min, the temperature is kept for 3 hours, and then cooled to 50°C.
[0114] S3: Water vapor is introduced with nitrogen as carrier gas to activate the coal-based hard carbon negative electrode material matrix after high-temperature carbonization in a tubular furnace. The temperature is raised to 900°C at a heating rate of 10°C / min and activated for 1h. The flow rate of the activator is 1ml / min to obtain a bituminous coal-based hard carbon negative electrode material.
[0115] Comparative Example 6
[0116] The specific steps and preparation method are the same as those in Example 1, except that the activation conditions are different.
[0117] Comparative Example 7
[0118] The specific steps and preparation method are the same as those in Example 1, except that the high-temperature carbonization temperature is different.
[0119] Comparative Example 8
[0120] The specific steps and preparation method are the same as those in Example 1, except that the activation conditions and high-temperature carbonization temperature are different.
[0121] Performance Testing
[0122] Electrochemical performance test: The bituminous coal-based hard carbon negative electrode material was used as the button battery negative electrode material powder, and the negative electrode sheet was prepared according to the ratio of main material: CMC: SP = 95:5:5. The metal sodium sheet was used as the positive electrode, and 1 mol / L NaPF 6 / EC+DEC (1:1) was used as the electrolyte, and a CR2032 button battery was installed in the glove box to ensure that H 2 O and O 2 The content of is less than 0.1ppm. The CR2032 button cell was tested using the Blue Electric Battery Test System, and the charge and discharge test was performed at a current density of 0.1C. The discharge cut-off voltage was 0V, and the charge cut-off voltage was 2.0V. The first-week reversible capacity and first-week coulombic efficiency of the material were obtained.
[0123] First cycle coulombic efficiency = (electricity released during the first discharge / electricity stored during the first charge) × 100%.
[0124] BET test conditions: Use JW-DX dynamic adsorption specific surface area analyzer to test the specific surface area of hard carbon materials using static method. Nitrogen is selected as adsorbent, argon is used as carrier gas, and the sample tube is placed in liquid nitrogen to maintain a low temperature test environment.
[0125] The experimental parameters of Examples 1-16 and Comparative Examples 1-8 are shown in Table 1, and the test results of Examples 1-16 and Comparative Examples 1-8 are shown in Table 2.
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131]
[0132] It can be observed from Examples 1-16 and Comparative Examples 1-8 that, on the one hand, Examples 1-16 exhibited first-week reversible capacity and first-week coulombic efficiency far superior to those of Comparative Examples 1-8. On the other hand, it can be observed from Examples 1-16 and Comparative Examples 1-8 that the theoretical specific surface area S of the coal-based hard carbon negative electrode material of Examples 1-16 prepared according to the method for regulating the specific surface area of the coal-based hard carbon negative electrode material proposed in this scheme is 理 Compared with the measured specific surface area S 实 The errors are all less than 3, indicating that the method for regulating the specific surface area of coal-based hard carbon negative electrode materials proposed in this scheme has high accuracy and practical significance.
[0133] It can be observed from Examples 1 and 16 and Comparative Example 1 that when coal-based raw materials are used to prepare hard carbon negative electrode materials, Examples 1 and 16 exhibit first-week reversible capacity and first-week coulombic efficiency that are far superior to those of Comparative Example 1. This may be because compared with other hard carbon negative electrode raw materials, the method proposed in this scheme is more suitable for preparing coal-based materials. Through the preparation method proposed in this scheme, we have obtained a coal-based hard carbon negative electrode material with high porosity and micropore ratio, which exhibits excellent first-week reversible capacity and first efficiency when used to prepare batteries.
[0134] From Example 1 and Comparative Examples 2-4, it can be observed that the preparation method of first acid washing, pre-carbonization, then steam activation, and finally high-temperature carbonization is very important. From Example 1 and Comparative Example 2, it can be observed that when the coal-based material is directly steam activated, the total pore volume of Comparative Example 2 is 0.027 cm 3 / g,I D / I G The value of is 1.38. At the same time, after being used to prepare the battery, the first-week reversible capacity and the first-week coulombic efficiency are not as good as those in Example 1. This may be because the pickling step can remove the ash in the coal-based material and improve the defects of the coal-based material. The pre-carbonization after pickling can pre-prepare pores in the coal-based material, laying the foundation for subsequent steam activation and carbonization. When pickling and pre-carbonization are not performed, the direct steam activation method may not be able to create enough pores and defects on the coal-based material. The total pore volume and I D / I G All of them are affected, which in turn affects the first-week reversible capacity and first-week coulombic efficiency of Comparative Example 2. While Example 1 and Comparative Example 3 demonstrate the necessity of steam activation for the preparation of coal-based hard carbon negative electrode materials. When steam activation is not performed, the coal-based hard carbon negative electrode materials lack sufficient pores and defects, resulting in the measured specific surface area S of Comparative Example 3. 实 The porosity and defect ratio cannot meet the requirements. At the same time, the lack of porosity and defects may further lead to an imbalance between the platform area and the slope area in the second week charge and discharge curve, which in turn leads to a decrease in the first week reversible capacity of the coal-based hard carbon negative electrode material and affects the first week coulomb efficiency. Example 1 and Comparative Example 4 reveal the effect of high-temperature carbonization. When high-temperature carbonization is not performed, the micropore volume ratio of the coal-based hard carbon negative electrode material is only 0.06%. This may be because when high-temperature carbonization is not performed, the pore size of the coal-based hard carbon negative electrode material activated only by steam is larger, so the micropore volume ratio is low. The low micropore volume ratio may make it difficult for sodium ions to be filled in the coal-based hard carbon negative electrode material, resulting in a decrease in the first week reversible capacity.
[0135] The order of steps for preparing coal-based hard carbon negative electrode materials is also very important. From Example 1 and Comparative Example 5, it can be seen that when high-temperature carbonization is first performed after acid washing and pre-carbonization, and when steam activation is performed, there are no micropores in Comparative Example 5, and at the same time, D / I G The carbonization temperature is 1.97, which may be because high temperature carbonization helps to promote the growth of graphite crystallites in coal-based hard carbon negative electrode materials, thereby achieving the shrinkage of the pore size of coal-based hard carbon negative electrode materials and the measured specific surface area S 实 The optimization of the present invention is that when the carbonization is carried out at high temperature first and then the steam activation is carried out, although the steam activation can prepare more and deeper pores, the pore size is too large and it is difficult to fill the sodium ions, so the capacity of the platform area decreases. On the other hand, the comparative example 5 in which the steam activation is finally carried out may also introduce more defect sites during the activation process, so that the capacity of the slope area is increased. Therefore, in the comparative example 5, N is 2.91, and I D / I G The first-week reversible capacity of the coal-based hard carbon negative electrode material is only 209.67 mAh / g, and the first-week coulombic efficiency is only 56.78%, which is much lower than that of Example 1.
[0136] After pickling and pre-carbonization, steam activation and high-temperature carbonization are performed. In order to prepare the coal-based hard carbon negative electrode material, it is necessary to further control the steam activation factor X and the high-temperature carbonization factor Y. From Example 1 and Comparative Example 6, it can be observed that when the activation temperature A is 750°C, the activation time B is 4h, and the activation flow rate C is 4ml / min, the steam activation factor X is 8. At this time, although the activation temperature A, the activation time B, and the activation flow rate C all meet the preparation conditions in the preparation step S2, X does not meet 2≤X≤7. Therefore, it can be observed that in Comparative Example 6, I D / I G It is 1.94, the volume of micropores accounts for only 2.09%, and the ratio N of the capacity of the platform area to the slope area in the second week of the charge and discharge curve is only 1.69, which means that even if the preparation conditions of the preparation step S2 are met, when the steam activation factor X is not met, the target coal-based hard carbon negative electrode material cannot be obtained. Therefore, in Comparative Example 6, the reversible capacity and coulombic efficiency in the first week are far inferior to those in Example 1.
[0137] Similarly, even if the high temperature calcination conditions in the preparation step S3 are met, when the calculated Y does not satisfy 0≤Y≤3, the ideal coal-based hard carbon negative electrode material cannot be obtained. From Example 1 and Comparative Example 7, it can be observed that when the high temperature carbonization temperature is 1700°C, although the conditions of the preparation step S3 are still met, at this time Y=4. Therefore, it can be observed that in Comparative Example 7, I D / I G The ratio of the capacity of the platform area to the capacity of the slope area in the second week charge-discharge curve is 1.82. The reversible capacity in the first week is 226.8 mAh / g, and the coulombic efficiency in the first week is 71.9%, which is still much lower than that in Example 1. This shows that on the basis of satisfying the above-mentioned preparation conditions and methods, it should be further ensured that Y satisfies 0≤Y≤3.
[0138] Furthermore, Comparative Example 8 shows a situation where neither 2≤X≤7 nor 0≤Y≤3 is satisfied. From Example 1 and Comparative Examples 6-8, it can be observed that when any one of 2≤X≤7 and 0≤Y≤3 cannot be satisfied, not only can the coal-based hard carbon negative electrode material whose charge and discharge curve of the second week satisfies 2.50≤N≤4.00 not be obtained, but also the measured specific surface area S cannot be obtained by S=[0.59EXP(X / 1.305)+24.39EXP(-Y / 2)-20.96]±Z. 实 When any one of X and Y is not satisfied, there will be a large error. Therefore, on the basis of satisfying the above preparation conditions, it is also necessary to satisfy 2≤X≤7, 0≤Y≤3.
[0139] Measured specific surface area S of coal-based hard carbon anode materials 实 , porosity and pore size are closely related to the conditions of steam activation and high-temperature carbonization. On the basis of satisfying 2≤X≤7, 0≤Y≤3, we further optimized and controlled the activation temperature, activation time, activator flow rate and high-temperature carbonization temperature. It can be observed from Examples 3-5 and 6-10 that Example 3-5 exhibits a better first-week reversible capacity and a higher micropore volume ratio than Example 6-10. This may be because when the activation temperature A is selected from 850℃-1000℃ and the activation time B is selected from 1h-3h, it helps to form more defects and more and deeper pores. At the same time, the control of the activator flow rate of 0.5ml / min-3ml / min can also effectively control the pore size, providing a better foundation for subsequent high-temperature carbonization. On this basis, the high-temperature carbonization temperature D is selected from 1300℃-1600℃, which helps to further improve the optimization effect of temperature on pore size and control the measured specific surface area S 实 , thereby obtaining a higher proportion of micropores and increasing the capacity of the platform area.
[0140] In Examples 1-2 and 3-5, the activation temperature, activation time, activator flow rate and high-temperature carbonization temperature are further optimized. Examples 1-2 show better first-week reversible capacity and micropore ratio than Examples 3-5 as a whole, and show a higher platform capacity (greater than 3.5) in the ratio of platform capacity to slope capacity in the second week charge-discharge curve. This may be because when A is selected from 800°C-900°C, since the steam activation process is an endothermic reaction, an activation temperature higher than 800°C helps to promote the reaction rate and form more pores; at the same time, when the activation time is selected from 1h-3h and the activator flow rate is selected from 0.5ml / min-1ml / min, more deep pores can be obtained, as well as a lower measured specific surface area S 实, thus laying a good foundation for high-temperature carbonization. At this time, the high-temperature carbonization temperature D is selected to be 1300℃-1500℃, which can give full play to the high-temperature carbonization effect and obtain a coal-based hard carbon negative electrode material with excellent charge and discharge capacity.
[0141] It can be observed from Examples 1 and 11 that when the particle size of the crushed bituminous coal is selected to be Dv50=5, Example 1 exhibits a higher micropore ratio than Example 11, and at the same time, the micropore ratio of the medium I D / I G It is 1.85. This may be because when the bituminous coal particle size is selected from Dv50=5-15μm, the particle size that satisfies Dv50=5-15μm helps to further cooperate with steam to achieve activation of the coal-based hard carbon negative electrode material matrix, thereby increasing the number of pores and defects. Therefore, Example 1 exhibits better first-week reversible capacity than Example 11.
[0142] In the step of preparing coal-based hard carbon negative electrode materials, the role of pre-carbonization is to initially form pores in the coal-based material to facilitate subsequent steam activation. It can be seen from Example 1 and Examples 12-13 that when the pre-carbonization time is 3 hours, Example 1 shows a higher total pore volume and micropore volume ratio than Examples 12-13, and thus shows a higher first-week reversible capacity. This may be because the 3-hour pre-carbonization time helps to form a higher number of pore prototypes, thereby laying a good foundation for subsequent steam activation; while Examples 1 and Examples 14-15 demonstrate the role of pre-carbonization temperature. When the pre-carbonization temperature is 750°C, it can prompt the coal-based material to form more and more evenly distributed pores, which also lays the foundation for subsequent steam activation. Therefore, Example 1 shows a higher first-week reversible capacity than Examples 12-15.
[0143] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A method for preparing a coal-based hard carbon negative electrode material using a coal-based material as a raw material, characterized in that: The steps include: S1: crushing and deashing the coal-based material, and then pre-carbonizing it to obtain a coal-based hard carbon negative electrode material matrix; S2: Activate the coal-based hard carbon negative electrode material matrix at 750°C-1000°C by 0.1ml / min-5ml / min of activator steam for 0.5-5h; S3: carbonizing the steam-activated coal-based hard carbon negative electrode material matrix at a high temperature of 1300-1800° C. and cooling the matrix to obtain a coal-based hard carbon negative electrode material; Among them, the preparation conditions satisfy X=(A-750) / 50+B+C, 2≤X≤7, A>750, Y=(D-1300) / 100, 0≤Y≤3, wherein X is the steam activation factor, A is the activation temperature (°C), B is the activation time (h), C is the activator flow rate (ml / min), Y is the high-temperature carbonization factor, and D is the high-temperature carbonization temperature (°C).
2. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The coal-based material is selected from any one or more of bituminous coal, sub-bituminous coal, anthracite and lignite.
3. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step S1, the coal-based material pulverization particle size is selected from Dv50=5-45 μm particle size, for example, it can be any one of 5 μm, 10 μm, 15 μm, 25 μm, 35 μm, and 45 μm; Preferably, in step S1, the coal-based material crushing particle size is selected from Dv50=5-15 μm; Preferably, in step S1, the coal-based material is deashed by pickling; Preferably, during the pickling process, the pickling solution is selected from a combination of two or more of hydrochloric acid, hydrofluoric acid, and nitric acid; Preferably, the mass ratio of the pickling solution to the coal-based material is selected from (3-7): 1; Preferably, after the acid washing is completed, the acid washed coal-based material is washed with deionized water and the washing liquid is tested. When the pH of the washing liquid is greater than 6, the washing is considered to be completed and the material is dried.
4. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The pre-carbonization in step S1 is carried out under an inert atmosphere; Preferably, the inert atmosphere is selected from any one of argon and nitrogen; Preferably, the pre-carbonization heating rate in step S1 is selected from 2°C / min-5°C / min.
5. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step S1, the pre-carbonization temperature is selected from 500-1000°C; Preferably, the pre-carbonization temperature in step S1 is selected from 600-800°C.
6. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step S1, the pre-carbonization time is selected from 1-5h; Preferably, the pre-carbonization time in step S1 is selected from 2-4 hours.
7. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step S2, the activator vapor is selected from deionized water vapor; Preferably, in step S2, the steam-activated carrier gas is selected from any one of argon and nitrogen; Preferably, in step S2, the heating rate is selected from 5°C / min-15°C / min.
8. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the high temperature carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from any one of argon and nitrogen; Preferably, the heating rate in step S3 is selected from 3°C / min-8°C / min; Preferably, the cooling temperature in step S3 is selected from 70°C to 25°C; Preferably, the high temperature carbonization time in step S3 is selected from 2h-6h.
9. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The activation temperature A is selected from 850°C-1000°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-3ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1600°C.
10. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The activation temperature A is selected from 800°C-900°C, the activation time B is selected from 1h-3h, the activator flow rate C is selected from 0.5ml / min-1ml / min, and the high-temperature carbonization temperature D is selected from 1300°C-1500°C.
Citation Information
Cited By
Method for preparing raw material of hard carbon negative electrode material from bituminous coal
CN120504312A
Method for preparing hard carbon negative electrode material raw material from bituminous coal
CN120504312B
Pre-sodium-modified negative electrode of sodium-ion battery and preparation method of pre-sodium-modified negative electrode
CN122158481A
Coal-based porous carbon, preparation method and application
CN122444180A